Research and Improvement of Adaptive Modulation and Coding Scheme for VDE-TER System - Li, Zhe; Li, Hai; Zhang, Qin (Journal of physics. Conference series, 2020)
VHF data exchange system (VDES) is an enhanced and updated system of AIS (Automatic Identification System) focused on maritime mobile communication, and VDE (VHF Data Exchange) is a main function of VDES. In this paper, we analyze the original adaptive modulation and coding (AMC) scheme of terrestrial VDE (VDE-TER). Because the original AMC scheme reserves several modulation and coding schemes for future use, we present an improved AMC scheme with more MCSs to increase system throughput. Simulation results have shown that the throughput performance of the proposed AMC scheme is improved.